TRICK OR TREAT ON SCARY STREET - Bass, Lance, 1979-; Garrigue, Roland, 1979- (New York : Union Square Kids, 2024)
Trick-or-treaters take a stroll down the scariest street in town on Halloween
Ages 3-8.
Keywords: Halloween -- Juvenile fiction; Picture books for children's; Stories in rhyme